Weak Organic Acids Decrease Borrelia burgdorferi Cytoplasmic pH, Eliciting an Acid Stress Response and Impacting RpoN- and RpoS-Dependent Gene Expression - Dulebohn, Daniel P.; Richards, Crystal L.; Su, Hua; Lawrence, Kevin A.; Gherardini, Frank C. (Frontiers in Microbiology, 2017)
The spirochete Borrelia burgdorferi survives in its tick vector, Ixodes scapularis, or within various hosts. To transition between and survive in these distinct niches, B. burgdorferi changes its gene expression in response to environmental cues, both biochemical and physiological. Exposure of B. burgdorferi cells to weak monocarboxylic organic acids, including those detected in the blood meal of fed ticks, decreased the cytoplasmic pH of B. burgdorferi in vitro. A decrease in the cytoplasmic pH induced the expression of genes encoding enzymes that have been shown to restore pH homeostasis in other bacteria. These include putative coupled proton/cation exchangers, a putative Na+/H+ antiporter, a neutralizing buffer transporter, an amino acid deaminase and a proton exporting vacuolar-type V0V1 ATPase. Data presented in this report suggested that the acid stress response triggered the expression of RpoN-RpoS-dependent genes including important virulence factors such as outer surface protein C (OspC), BBA66, and some BosR-dependent genes. Because the expression of virulence factors, like OspC, are so tightly connected by RpoS to general cellular stress responses and cell physiology, it is difficult to separate transmission-promoting conditions in what is clearly a multifactorial and complex regulatory web.